La lingua italiana tra passato e futuro - Maraschio, Nicoletta (Lectio Magistralis, 2015)
This book outlines a short profile of Italy's linguistic history, and discusses some current problems related to globalization, the values of the mother tongue and multilingualism, and the need to re-found the Italian and European linguistic policy on a new basis. Contemporary Italian is a particularly stratified cultural asset in which, alongside the many new elements, one can grasp the clear and precious signs of a very strong connection with the past. Today, in the European scene, Italy indeed stands out for its accentuated multilingualism and the long duration of its national language. On the one hand, the extraordinary animal and plant biodiversity in the country corresponds to an extraordinary cultural and linguistic diversity; on the other, the Italians feel that the language used by Dante, Petrarca and Boccaccio still belongs to them, and has fundamental traits coinciding with their own. Such richness is particularly appreciated abroad (as evidenced by the growing demand for Italian speakers in the world) and deserves to be better acknowledged by the younger generations. It also deserves to be protected and valued with appropriate tools, starting with a decisive rethinking of the country's linguistic policy.